Assessing the Feasibility of Retrospective and Prospective Clinical Audit in Farm Animal Veterinary Practice - Waine K; White C; Dean RS; Hudson C; Huxley JN; Brennan ML (MDPI (Basel, Switzerland), 2021)
As a quality improvement tool, clinical audit has been extensively described in the medical literature. There is scant literature on the use of clinical audit in the farm animal veterinary setting. This study describes the process and feasibility of prospective and retrospective data collection for farm animal clinical audit performed at three different farm animal practices in the United Kingdom. Retrospective clinical audit was difficult in all three practices due to barriers in establishing diagnosis and patient identity from clinical records. Prospective data collection proved feasible but depended on adequate case accrual and practitioner engagement. The decision to conduct clinical audit retrospectively or prospectively will depend on the topic to audit, the availability of data and the wishes of the team members involved. Further work is required looking at the use of clinical coding and alternatives to using practice management software to improve retrospective data availability for clinical audit.
Keywords: clinical audit; farm animal practice; farm animal veterinary medicine; prospective clinical audit; quality improvement; retrospective clinical audit